A novel material of HfScMo2VO12 with negative thermal expansion and intense white-light emission. Issue 59 (2nd June 2016) - Cheng, Yongguang; Liang, Yuan; Ge, Xianghong; Liu, Xiansheng; Yuan, Baohe; Guo, Juan; Chao, Mingju; Liang, Erjun
Abstract : A novel material of HfScMo2 VO12 with negative thermal expansion (NTE) and intense white-light emission is presented. Abstract : A novel material of HfScMo2 VO12 with negative thermal expansion (NTE) and intense white-light emission is presented. Structural analysis shows that it adopts an orthorhombic structure with the space group Pbcn and exhibits excellent NTE over a wide temperature range. The linear coefficient of thermal expansion was measured to be −2.78 × 10 −6 K −1 (−150 to 675 K) and −2.99 × 10 −6 K −1 (300–780 K) by dilatometers and α l = −2.11 × 10 −6 K −1 from temperature-dependent X-ray diffraction. Besides the NTE property, HfScMo2 VO12 possesses intense wide-band photoluminescence (PL) covering the visible region. The commission International de I'Eclairage (CIE) chromaticity coordinate is (0.27, 0.39) at room temperature and (0.33, 0.36) at 10 K, respectively. The integration of low NTE with intense white-light emission suggests potential applications of this material in white light emission diodes and other devices.